The Development Strategy of Soybean Agribusiness in PT Lentera Panen Mandiri - Dewi Nurpitasari; Lestari Rahayu Waluyati; Jangkung Handoyo Mulyo (Agro Ekonomi, 2018)
The aims of this study are to identify both internal and external factors of agribusiness in PT Lentera Panen Mandiri (PT LPM), map the company’s position, and determine its development strategy. Main data used in this study is primary data obtained from stakeholders of PT LPM by direct interview. Strength, Weakness, Opportunity and Threat (SWOT) of soybean agribusiness in PT LPM were identified in this study and followed by determining the company’s position using SWOT diagram. Alternative srategies were derived from the SWOT matrix and prioritized using Quantitative Strategies Planning Matrix (QSPM) analysis. The results of this study identified 5 strengths, 7 weaknesses, 9 opportunities, and 6 threaths with the highest factors consisted as "company's commitment to supervise and foster farmers and suppliers", "is time-consuming sorting process and potency of mixed between rice and soybean", "opportunity to increase the  productivity of soybean at farmer level ", and "uncommit suppliers to supply only from areas that have been approved by the company" respectively. Based on the  SWOT diagram, soybean agribussiness in PT LPM positioned in Quadrant I, which mean that the company should apply Agressive Strategy or Strength – Opportunity (S-O) strategy. Based on the SWOT Matrix, 5 alternative of S-O strategies were derived. Based on the QSPM analysis, strategy for guarding and coaching farmers through patnership scheme is the first priority with Total Attarctive Score (TAS) is 12.9.